Assessing the effects of empowerment and emotions on job satisfaction in hotel service environments - Abdul Aziz, Yuhanis (2011)
Employee empowerment is receiving increased attention in services marketing and services management literature. Emotion management is also becoming important in the workplace, particularly in the service industry. While empowerment has been encouraged in the hotel industry, a basic understanding on the possible relationship between empowerment and emotions has yet to emerge. Evidence on the effect of empowerment and emotions on job satisfaction is also limited. Therefore, the objectives of the study are threefold: to empirically investigate the relationship of empowerment on both positive and negative emotions, to test whether the empowerment has association on employee’s job satisfaction and to examine the relationship of positive and negative emotions on job satisfaction. A number of notable findings are found from data analysis. The findings signify a significant positive relationship between empowerment and positive emotions whilst indicating a negative relationship with negative emotions. The results also point out that both empowerment and positive emotions have a significant impact on employee’s job satisfaction. Moreover, as hypothesized, the results support the negative relationship between negative emotions and job satisfaction. The results suggest significant implications for hotel managers and academicians, in addition to preparing a platform for future research.